"I want to know everything": a qualitative study of perspectives from patients with chronic diseases on sharing health information during hospitalization - Marge Benham-Hutchins; Nancy Staggers; Michael Mackert; Alisha H. Johnson; Dave deBronkart (BMC, 2017)
Abstract Background Patient-centered care promotes the inclusion of the most prominent and important member of the health care team, the patient, as an active participant in information exchange and decision making. Patient self-management of a chronic disease requires the patient to bridge the gap between multiple care settings and providers. Hospitalizations often disrupt established self-management routines. Access to medical information during hospitalization reflects patients' rights to partner in their own care and has the potential to improve self-management as well as promote informed decision making during and after hospitalization. The objectives of this study were to elicit the perspectives of patients with chronic disease about desired medical information content and access during hospitalization. Methods This exploratory study incorporated a qualitative approach. The online survey included the research team created open and limited response survey, demographic and hospital characteristic questions, and the Patient Activation Measurement instrument (PAM®). Convenience and social media snowball sampling were used to recruit participants through patient support groups, email invitations, listservs, and blogs. The research team employed descriptive statistics and qualitative content analysis techniques. Results The study sample (n = 34) ranged in age from 20 to 76 (μ = 48; SD = 16.87), Caucasian (91%, n = 31), female (88%, n = 30) and very highly educated (64%, n = 22 were college graduates). The PAM® survey revealed a highly activated sample. Qualitative analysis of the open-ended question responses resulted in six themes: Caring for myself; I want to know everything; Include me during handoff and rounds; What I expect; You're not listening; and Tracking my health information. Conclusions This study revealed that hospitalized patients want to be included in provider discussions, such as nursing bedside handoff and medical rounds. Only a few participants had smooth transitions from hospital to home. Participants expressed frustration with failures in communication among their providers during and after hospitalization and provider behaviors that interfered with patient provider communication processes. Patients also identified interest in maintaining their own health histories and information but most had to "cobble together" a myriad of methods to keep track of their evolving condition during hospitalization.